2018
DOI: 10.1158/0008-5472.can-18-1652
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Explant Responses to STING Ligands: Personalized Immunosurgical Therapy for Head and Neck Squamous Cell Carcinoma

Abstract: Surgeons have unique access to tumors enabling them to apply immunotherapies to resection margins as a means to prevent local recurrence. Here, we developed a surgical approach to deliver stimulator of interferon genes (STING) ligands to the site of a purposeful partial tumor resection using a gel-based biomaterial. In a range of head and neck squamous cell carcinoma (HNSCC) murine tumor models, we demonstrate that although control-treated tumors recur locally, tumors treated with STING-loaded biomaterials are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…40). IL-10 was identified as a prominent immunosuppressive factor in MOC2-derived tumors (41); thus, we additionally assessed the transcription levels of IL-10. We found that IL-10 was trending decreased in the NLRX1-deficient tumors (P = 0.08) (Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40). IL-10 was identified as a prominent immunosuppressive factor in MOC2-derived tumors (41); thus, we additionally assessed the transcription levels of IL-10. We found that IL-10 was trending decreased in the NLRX1-deficient tumors (P = 0.08) (Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent unbiased screen using HNSCC cell-effector immune cell coculture identified the IFN-I pathway as a central signal that maintains HNSCC sensitivity to immune killing (14). IFN-I downstream cytokines and chemokines improve APC and effector trafficking to the tumor mass and maintain a TME that favors APC maturation and cross-priming of CD8 + CTLs (16,19,22,41,(46)(47)(48)(49), thereby driving antitumor immunity. A number of strategies are being assessed to activate STING-mediated innate immune sensing and enhance immune priming.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of DDS include their ability to profoundly alter and improve drug pharmacokinetics, provide targeted drug delivery, and therefore alleviate TRAEs whilst enhancing therapeutic outcomes [ 125 , 126 , 127 , 128 ]. The three main DDS discussed here are liposomes, polymers and hydrogels ( Table 3 ) [ 14 , 123 , 124 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. Liposomes are cationic lipid structures with an aqueous core, making them great candidates for encapsulating negatively charged, hydrophilic CDN compounds [ 138 , 139 , 140 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Relative to the free controls, the loaded hydrogel at the resection site significantly inhibited local 4T1 breast cancer recurrence and removed the metastases, by increasing the DC, T cell and NK cell amounts and type I IFN secretion. Similarly, Gough et al mixed CDA in phosphate‐buffered saline buffer with Matrigel at 4°C and dropped the liquid into the resection site . At body temperature, the liquid formed an amorphous solid gel.…”
Section: Sting Agonistsmentioning
confidence: 99%